A conceptual framework for examining the relationship between high performance system and organizational citizenship behaviour - Pangil, Faizuniah; Md. Salleh, Salniza (Penerbit Universiti Utara Malaysia, 2008)
Despite the objective of high performance work system(HPWS) to provide a work environment that is conducive for high performance, most literature on HPWS is more concerned with its effect on organisational performance. There are only a number of studies that have examined the effect of HPWS on individual attitudes and behaviour, such as organisational citizenship behaviour (OCB). The limited number of studies on the examination of HPWS and OCB is unfortunate because OCB is considered an important element in employee's performance that can help the organisation to sustain its competitive advantage. Hence, the purpose of this paper is to provide a conceptual framework for examining the relationship between HPWS and employee OCB, in which job satisfaction and organisational commitment play the mediating role in this relationship.